2021
DOI: 10.1017/s1360674321000022
|View full text |Cite
|
Sign up to set email alerts
|

English verbs can omit their objects when they describe routines

Abstract: Which normally transitive verbs can omit their objects in English (I ate), and why? This article explores three factors suggested to facilitate object omission: (i) how strongly a verb selects its object (Resnik 1993); (ii) a verb's frequency (Goldberg 2005); (iii) the extent to which the verb is associated with a routine – a recognized, conventional series of actions within a community (Lambrecht & Lemoine 2005; Ruppenhofer & Michaelis 2010; Levin & Rapaport Hovav 2014; Martí 2010, 2015). To opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Verbs might be formally specified for optional objects in the lexicon, but the reason why some verbs (or verb classes) and not others come to carry that specification can have a semantic or pragmatic explanation. Glass (2021) appeals to routines as a possible explanation. She presents experimental and corpus evidence suggesting that verbs that describe routines are more likely to allow object omission than verbs that do not describe routines.…”
Section: Argument Omission In Englishmentioning
confidence: 99%
“…Verbs might be formally specified for optional objects in the lexicon, but the reason why some verbs (or verb classes) and not others come to carry that specification can have a semantic or pragmatic explanation. Glass (2021) appeals to routines as a possible explanation. She presents experimental and corpus evidence suggesting that verbs that describe routines are more likely to allow object omission than verbs that do not describe routines.…”
Section: Argument Omission In Englishmentioning
confidence: 99%
“…This strategy uses the sub-forum structure of Reddit, which is organized into large, general-interest forums such as r/AskReddit, as well as smaller forums dedicated to specialized interests such as r/Cookingwhich I take as distinct communities of practice with their own conventions (Zhang et al 2017;Del Tredici & Fernández 2018). Following Glass (2021), I use a Fisher Exact Test to compare the possessive and non-possessive counts of the same noun in AskReddit versus in various specialized subreddits.…”
Section: Towards Testable Predictions: More Conventional More Relationalmentioning
confidence: 99%
“…To approximate convention in corpus data, the article uses a noun's per-million-word frequency (the more conventionally people interact with an entity, the more they might talk about it) and its ratio of non-possessive definite to indefinite tokens (the more conventionally people interact with an entity, the more they might treat its referent as discourse-familiar and thus definite). These metrics are used (section 5) to compare across nouns in data from AskReddit, a large, general-interest discussion forum; and to compare across communities in data from Reddit's different specialty sub-forums, leveraging the assumption (Glass 2021) that conventions vary across such communities. Across nouns, it is found that within a given ontological class (such as ‘artifact’ or ‘natural kind’), more frequent nouns are more often possessive ( phone is more frequent and more often possessive than lamp , cat is more frequent and more often possessive than horse ).…”
Section: Introductionmentioning
confidence: 99%